Dari Benteng Kuto Gawang Ke Kuto Besak : Analisis Faktor Politik Pada Tahun 1780 - R.M. Apriza Zulkarnain (Tanjak: Sejarah dan Peradaban Islam, 2023)
This study describes the change of Kuto Gawang Fortress to Kuto Besak in 1780 Palembang City. This study uses political theory, from an antropological point of view there is a politics that occurs gradually. This method uses historical methods for sistematic and objective reconstruction of the past through the stages of data collection, evaluation, verification, synthesizing evidence of fact, and obtaining evidence of strong conclusions. The method approach uses qualitative research method which are literature reviews both journals, magazines, and the internet. The data used is using primary data and secondary data. Data collection techniques, observation, interview documentation. The conclusion of this research us that Kuto Besak and Kuto Gawang forts are one of the historical relics of the past in the city of Palembang. The Kuto Gawang palace which was founded by Ki Gede Ing Suro who was a follower of Aria Jipang who fled to Palembang from 1552 to 1659 Kuto Gawang was destroyed by the Dutch.